Short report: transient antibody response in Taenia solium infection in field conditions-a major contributor to high seroprevalence. (2001)
ABSTRACT: The discordance between extremely high seroprevalence of Taenia solium antibodies in disease-endemic populations, relatively few symptomatic cases of neurocysticercosis, and high background levels of putatively inactive brain lesions (mainly calcifications) in seronegative controls have confused researchers, clinicians, and epidemiologists in the last decade. We reviewed longitudinal serologic data from general population serosurveys in 3 different diseaseendemic areas of Peru and Colombia and found that 40% of seropositive people were seronegative when resampled after 1 year (3 surveys) or after 3 years (1 survey). Transient antibodies may have significant implications for the epidemiology of and immunity to this disease.